APPROACHES TO DISTANCE LEARNING IN PHYSICAL EDUCATION IN COLLEGES DURING WAR - Koloskova, Nadiya (The Modern Higher Education Review, 2022)
Lockdowns and the introduction of anti-epidemic measures to prevent the spread of the acute respiratory disease COVID-19, the war conflict in Ukraine resulted in the implementation of online education, significantly limited the access of students to college gyms and reduced the number of face-to-face classes under the guidance of teachers. This had a negative impact on the health of students. According to the results of the medical examination, about 28% of the students of the "Universum" Vocational College are assigned to the preparatory and special medical health groups. Statistics show that every third of young people have various abnormalities in their health. One of the reasons for this is insufficient motor activity. With the introduction of martial law in Ukraine, the situation regarding the organisation of the educational process has deteriorated significantly. The cyclical commissions of physical education of colleges faced the question of finding new forms and methods of organising classes, taking into account the challenges of the times. The author analysed the advantages and disadvantages of physical education for students in the period of implementation of distance and blended learning. It has been established that mixed training in physical education is a more flexible and diverse form of conducting classes. The transition to a distance and mixed form of education in physical education requires the development of new approaches to the methodology of organising classes, the establishment of personally significant priorities and needs for the physical development of students, the modernisation of existing learning technologies and the development of new mechanisms for effective cooperation between teachers and students.